Bryostatin I inhibits growth of breast cancer cells through the inhibition of synuclein-A expression (Bangladesh Journal of Pharmacology, 2016)
The present study was aimed to investigate the effect of bryostatin I on the expression of synuclein-A in breast cancer cells. Western blot analysis showed a significant (p